THE INFLUENCE OF CUSTOMER SATISFACTION, CUSTOMER DELIGHT AND CUSTOMER TRUST ON CUSTOMER LOYALTY IN THE SHOPEE MARKETPLACE - Mujito; Tika Kartika Asri; Wawan Hari Subagyo; Eidelweijs Andririnjani Putri; Andri Catur Trissetianto (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of Customer Satisfaction, Customer Delight, and Customer Trust on customer loyalty in the Shopee marketplace. A quantitative approach was employed with data collected through questionnaires to active Shopee users. Multiple linear regression results show that the three independent variables simultaneously have a significant effect on customer loyalty, but only Customer Trust has a significant partial effect. The Adjusted R Square indicates that the independent variables explain approximately 41.4% of the variation in customer loyalty. These findings highlight the importance of building customer trust as a key strategy in maintaining loyalty on e-commerce platforms.